Research on ultrasonic vibration assisted repair technology of high temperature and high pressure parts - Che Lei; Sun Wenlei; Zhang Guan; Han Jiaxin (Functional Materials, 2018)
This paper studies the ultrasonic vibration assisted lifting laser cladding technology. Firstly, the simulation model of ultrasonic vibration-enhanced Ni60 self-fluxing alloy powder coated with 45 steel substrate is established, and the variation law of temperature field and temperature gradient in ultrasonic vibration strengthening process are analyzed by using Ansys finite element analysis software. After that, the microstructure, microhardness and surface roughness of the cladding layer are compared with that of the cladding test blocks with and without ultrasonic vibration. The results show that as the ultrasonic frequency increases or the scanning speed decreases, the temperature increases everywhere along the Z-axis, and the temperature gradient from the cladding layer to the interface area decreases. Compared to the cladding layer without ultrasonic vibration, the microstructure of the cladding layer obtained by applying ultrasonic vibration is finer and denser due to the effect of ultrasonic cavitation, and the microhardness is increased by 1.37 times and the surface roughness is reduced by 36.6%.